Study on underwater noise characteristics and mechanism of discharge flow from wide-crested weir - Qingxiang Shui; Daguo Wang; Yuxin Chen; Tao Yu; Yi Fan; Yang Dai (PLoS ONE, 2026)
To provide theoretical guidance and technical support for mitigating underwater noise generated by discharge flow from wide-crested weirs, this study integrates physical experiments and numerical simulations. The effects of inflow, downstream static water depth, and weir height on underwater noise sound pressure level (SPL) and fluctuating pressure SPL were analyzed using correlation methods, and the time–frequency variation mechanism of underwater noise was investigated through wavelet analysis. Results show a significant positive correlation between underwater noise SPL and fluctuating pressure SPL, indicating that fluctuating pressure can be used to characterize underwater noise variation. Downstream static water depth exerts the greatest influence, with a negative correlation to SPL, whereas inflow and weir height have relatively smaller effects, both showing positive correlations. As inflow and weir height increase, and static water depth decreases, the mid-frequency range (400 ~ 600 Hz) exhibits high energy that decays rapidly. Fluctuating pressure at the measuring point is affected by the impingement of the main flow tongue on the downstream water body, vortex structure variation and breakup, and sound waves radiated from bubble collapse.